PELATIHAN TEKNIK JEUX DE RÔLES-ACTES DE PAROLE BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN BAHASA PRANCIS UNTUK GURU SMA/SMK/MA SE-JAWA BARAT - Mutiarsih, Yuliarti; Sunendar, Dadang; Hardini, Tri Indri; Karimah, Iim Siti; Amalia, Farida (Dimasatra, 2022)
This community service program is based on the responsibility and enthusiasm of all lecturers in the Department of French Language Education FPBS UPI in implementing one of Tri Dharma Perguruan Tinggi. The aim is to disseminate the findings of the research that has been carried out, so that it is conveyed and beneficial to the community and to answer the needs of teachers for improve their ability to manage teaching and learning processes, especially pedagogic abilities. On the other hand, this community service aims to train the jeux de rôles-actes de parole technique for SMA/SMK/MA teachers in West Java. This program is expected to produce outputs in the form of increasing the scientific insight of teachers about foreign language learning techniques, especially French which is expected to improve the quality of the learning process which in turn has an impact on improving the quality of student learning outcomes. Other outputs of this community service are articles and papers presented at the national or international level, collaborations and publications.